Strength characteristics and micro-mechanism of shield tunneling fine muck synergistically improved with fiber reinforcement and solid waste-based gelling agent - Xiuting Su; Xixi Huang; Jian Chen; Pooya Saffari; Xiuling Li; Zheng Li; Afshin Asadi (Case Studies in Construction Materials)
Slurry shield tunneling in strata with high clay content, such as silty clay and argillaceous sandstone, often generates a significant amount of waste fine muck characterized by high water content and compressibility. Curing and improving this muck is essential for its large-scale utilization as a resource. This study explores the synergistic improvement of shield tunneling fine muck by combining the solid-waste-based gelling agent (SWGA) with basalt fiber (BF). It analyzes the effects of basalt fiber content, as well as dry-wet and freeze-thaw cycles, on the strength of the solidified body. The discussion focuses on the stress-strain relationship, unconfined compressive strength, and microscopic cementation behavior of the solidified body, while also examining the erosion effects caused by dry-wet and freeze-thaw cycles. The test results indicate that the mechanical properties of the shield tunneling fine muck after solidification with SWGA-BF were significantly improved compared to those solidified with silicate cement. Additionally, its failure mode transitioned from brittle failure to ductile failure, resulting in significant improvements in macro- and micro-mechanical properties. A threshold for basalt fiber content was observed at 0.5 %. When the fiber content was below this threshold, the three-dimensional network structure formed by fibers effectively inhibited deformation and improved strength. However, when the fiber content exceeded 0.5 %, the fiber knotting and clustering inside the specimen led to a decrease in strength. Furthermore, dry-wet and freeze-thaw cycles partially disrupted the cementation between the fibers, hydration products, and muck to a certain extent, though basalt fiber significantly enhanced the durability of the solidified body against these cycles. The findings provide theoretical support and methodological guidance for understanding the strength evolution mechanism and durability of the improved shield tunneling fine muck.